POLITICAL EDUCATION TO INCREASE BEGINNER VOTER PARTICIPATION IN THE 2019 GENERAL ELECTIONS - Danang Sa'adawisna; Bayu Karunia Putra (Awang Long Law Review, 2023)
This article aims to find out the implementation of political education programs to increase the participation of first-time voters in the 2019 general elections in Malang Regency. This topic is important and interesting, because the increase in community participation has a great influence in holding elections, coupled with socialization and political education which is one of the strong foundations for building the level of voter participation in using their right to vote as well as possible, especially during elections. general public in 2019. This research method is a method that uses a descriptive qualitative approach, where this method utilizes qualitative data and is described descriptively. Sources of data in this study were obtained through interviews, observation, and online media. Data collection and data analysis techniques in this study were interviews, observations, and online media conducted by researchers to collect, explore, and gather valid, complete, and relevant information relating to the topic of the problem which is the object of research. The research finds that, with regard to political education, it is very useful as a strategy to increase a high participative attitude in using their right to vote as best as possible, because this strategy is a good step to encourage them to become agents of change, so that awareness of rights politics, democracy, and community participation can be further improved.